Management of Donor Site of a Transposition Flap - Tripathi, F. M.; Sinha, J. K.; Bhattacharya, V. (Indian Journal of Plastic Surgery, 1980)
Present case veport illustrat=s one of the methods for management of donor site of a transpo ition flap by twa transposition flaps.